2011
DOI: 10.1039/c0cp01488e
|View full text |Cite
|
Sign up to set email alerts
|

Radon hydrides: structure and bonding

Abstract: Quantum chemical calculations, using gradient-correct density functional at the BP86 level in conjunction with TZ2P basis sets, have been carried out for the radon hydrides HRnY (with Y = F, Cl, Br, I, CCH, CN, and NC). The bonding in HRnY is studied using different bond ruptures, establishing the role of those stabilizing (and destabilizing) factors that prevent these species to be dissociated. Although all HRnY systems studied here are bound equilibrium structures, they are metastable species with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…In recent years there have been several papers that discussed other similar radon compounds, those of the type HRnX where X could be fluorine [19] or other halogens and related ligands [20]. These papers concluded that radon bonds very similarly to xenon, but the bond lengths and interaction energies tend to be slightly larger, in agreement with expectations based on periodic trends for the other noble gases.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In recent years there have been several papers that discussed other similar radon compounds, those of the type HRnX where X could be fluorine [19] or other halogens and related ligands [20]. These papers concluded that radon bonds very similarly to xenon, but the bond lengths and interaction energies tend to be slightly larger, in agreement with expectations based on periodic trends for the other noble gases.…”
Section: Introductionsupporting
confidence: 56%
“…This also allowed for an estimate of the stretching vibrational frequency for this bond. The error introduced by fixing the M-X distance is expected to be small, as previous theoretical [5,6,20,25] and experimental [2][3][4] work on these and similar systems has shown that these bond lengths are not greatly affected by the noble gas bonding to the metal. These calculations were performed at the MP2 level, with some test cal- energies were calculated at the MP2 geometries to obtain a better estimate of the interaction energies.…”
Section: Methodsmentioning
confidence: 88%
“…On the one hand, resonance bonding is an essential feature of H-Xe bonding in HXeY. On the other hand, we note that earlier studies on the bonding of noble-gas hydrides have already analyzed the leading resonance structure H-Xe + Y − (Pérez-Peralta et al, 2009;Juarez et al, 2011). In the next section, we will carry out detailed analyses on H − Xe + -Y, as well as H-Xe + Y − .…”
Section: H-xe Resonance Bonding In Hxeymentioning
confidence: 94%
“…Two articles by Christe [18] and Gerber [19] entitled "A Renaissance in Noble Gas Chemistry" and "New Chemistry of the Noble Gas Elements: Novel Molecules, Polymers and Crystals" review the recent achievements in NG chemistry. A series of theoretical studies exploring the viability of NG compounds by the groups of Frenking, [32][33][34][35][36][37][38][39] Grandinetti, [40][41][42][43] and Merino [44,45] should also be mentioned here. [22] The probable existence of endohedrally NG trapped cage-like structures has been investigated both theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%